Analisis Kepuasan Masyarakat Terhadap Pelayanan 27 Puskesmas di Kabupaten Mojokerto Berdasarkan Indeks Kepuasan Masyarakat - Kuswadi Rustam (HOME, 2020)
The Measurement of community satisfaction in the healthy sector is an important element in the evaluation of the performance of the Govermnent in Mojokerto Regency. In this case, the Public Health Centre (PHC) should become a public institution based on community-based services which is the best, efficient, and more effective. For this reason, research on the level of satisfaction of PHC in Mojokerto is aimed to determine the correlation among satisfaction index and the community expectations in a PHC services in Mojokerto Regency. The method was used is a qualitative descriptive, the research is designed to combines qualitative and quantitative data. The object of the research is the people who use the PHC in 27 sub-districts in Mojokerto district. The sampling technique used in this study was purposive accidental sampling at the research location with 150 respondents per PHC location. Respondent data collection was carried out by interview and questionnaire techniques. the obtained data then calculated the weighted average value, community satisfaction index (IKM) and conversion in the form of a table of perception and IKM values. The results of the analysis show that the highest average conversion value of each service element of the 27 PHC is the conversion value of the cost / tariff element (U4) of 89.01 or reaches the service quality value is A. While the lowest average conversion value is the service element of complaint handling. (U4) 84.40, is in the value of service quality is B, while the other 20 of other PHC status is Good IKM.